2015
DOI: 10.1371/journal.pone.0141146
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Activation of the Vastus Intermedius Muscle during Isometric Hip Flexion

Abstract: Although activity of the rectus femoris (RF) differs from that of the other synergists in quadriceps femoris muscle group during physical activities in humans, it has been suggested that the activation pattern of the vastus intermedius (VI) is similar to that of the RF. The purpose of present study was to examine activation of the VI during isometric hip flexion. Ten healthy men performed isometric hip flexion contractions at 25%, 50%, 75%, and 100% of maximal voluntary contraction at hip joint angles of 90°, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
0
9
0
4
Order By: Relevance
“…A study reported that a smaller VI thickness was associated with the knee extension torque, which is related to the performance of explosive movements [ 13 ]. In addition, another study showed that the VI is activated during the recovery phase of running, which could indicate that it provides knee joint stabilization as an antagonist during hip flexion [ 35 ]. A study with patients who had undergone ACLR showed VI thickness reduction to result in decreased knee extension torque and the same study suggested that increasing VI thickness by rehabilitation after ACLR could be the key factor for the proper restoration of knee function [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that a smaller VI thickness was associated with the knee extension torque, which is related to the performance of explosive movements [ 13 ]. In addition, another study showed that the VI is activated during the recovery phase of running, which could indicate that it provides knee joint stabilization as an antagonist during hip flexion [ 35 ]. A study with patients who had undergone ACLR showed VI thickness reduction to result in decreased knee extension torque and the same study suggested that increasing VI thickness by rehabilitation after ACLR could be the key factor for the proper restoration of knee function [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigators have tried to measure the electromyographic activity of the VI by surface and needle electrodes, on the assumption that the inferolateral part of the QF would represent the VI as suggested by magnetic resonance imaging (Watanabe and Akima, 2009;Saito and Akima, 2015;Tomita et al, 2015). However, this study revealed beyond doubt that this muscular part represented the VL-O, not the VI.…”
Section: Discussionmentioning
confidence: 81%
“…Hip flexion assistance could release pressure of hip flexion muscle groups and decrease the strength of the short head of biceps femoris arisen from the lateral lip of the linea aspera. Hip extension assistance descended the strength of vastus intermedius which had a closer route for the excitatory impulse on α-motoneuron of the vastus intermedius than other knee muscle groups, making vastus intermedius more sensitive to external stimulus [54,55]. As for knee flexion assistance, the strength of the short head of the biceps femoris dropped and the strength of vastus intermedius fell conspicuously.…”
Section: ⅳ Discussionmentioning
confidence: 99%